Cosmopolitanism and women's fashion in Ghana : history, artistry and nationalist inspirations - Richards, Christopher L. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Drawing on extensive archival research and interviews, this book delves into the rich world of Ghanaian fashion, demonstrating how, over time, local dress styles and materials have been fused with global trends to create innovative, high fashion garments that reflect a distinctly Ghanaian cosmopolitanism. Ghana has a complex and diverse fashion culture which was in evidence before independence in 1957 and has continued to grow in reputation in the postcolonial period. In this book, Christopher Richards reflects on the contributions of the country's female fashion designers, who have employed fashion to innovate existing, culturally relevant dress styles, challenge gendered forms of dress, and make bold statements regarding women's sexuality. Treated as artworks, the book examines specific garments to illustrate the inherent complexity of their design and how fashion is often embedded with a blending of personal histories, cultural practices and global inspirations. Reflecting in particular on the works of Laura Quartey, Letitia Obeng, Juliana Kweifio-Okai, Beatrice Arthur, and Aisha Ayensu, this book makes an important and timely contribution to art history, fashion studies, anthropology, history, women's studies and African Studies"--
Introduction: The Many Modes of (African) Fashion -- Accra's Pre- and Independence-Era Fashion Cultures -- The Forerunners of Ghana's Fashion Designers: Letitia Obeng and Laura Quartey -- "Paris-Trained, Osu-Domiciled": Juliana "Chez Julie" Kweifio-Okai, Ghana's First Fashion Designer -- "I Don't Do Nice; it Has to be Interesting": The Designs of Beatrice "Bee" -- "The Spirit of the African Woman": Aisha Ayensu and her Brand Christie Brown -- The Future of Ghanaian, and African Fashion.
Keywords: Fashion -- Ghana; Fashion designers -- Ghana; Fashion and art; Cosmopolitanism -- Ghana; ART / African; ART / History / General